Construction of Type 2 Poly-Changhee Polynomials and Its Applications. (10th December 2021) - Muhiuddin, Ghulam; Khan, Waseem Ahmad; Younis, Jihad
Abstract : In this paper, we introduce type 2 poly-Changhee polynomials by using the polyexponential function. We derive some explicit expressions and identities for these polynomials, and we also prove some relationships between poly-Changhee polynomials and Stirling numbers of the first and second kind. Also, we introduce the unipoly-Changhee polynomials by employing unipoly function and give multifarious properties. Furthermore, we provide a correlation between the unipoly-Changhee polynomials and the classical Changhee polynomials.